2017
DOI: 10.1016/j.molcel.2017.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an RNA Polymerase III Regulator Linked to Disease-Associated Protein Aggregation

Abstract: SummaryProtein aggregation is associated with age-related neurodegenerative disorders, such as Alzheimer’s and polyglutamine diseases. As a causal relationship between protein aggregation and neurodegeneration remains elusive, understanding the cellular mechanisms regulating protein aggregation will help develop future treatments. To identify such mechanisms, we conducted a forward genetic screen in a C. elegans model of polyglutamine aggregation and identified the protein MOAG-2/LIR-3 as a driver of protein a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 86 publications
(105 reference statements)
0
16
0
Order By: Relevance
“…In Sin et al (2017), a forward genetic screen was performed on worms that express 40 glutamine (Q) repeats fused to YFP (here referred as Q40 worms) to search for mutants with reduced number of polyglutamine aggregates (Sin et al, 2017) (Figure 3A). The study identified a regulator of RNA polymerase III transcription– moag-2/lir-3 –as an aggregation-promoting factor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Sin et al (2017), a forward genetic screen was performed on worms that express 40 glutamine (Q) repeats fused to YFP (here referred as Q40 worms) to search for mutants with reduced number of polyglutamine aggregates (Sin et al, 2017) (Figure 3A). The study identified a regulator of RNA polymerase III transcription– moag-2/lir-3 –as an aggregation-promoting factor.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoblots were quantified by densitometry using ImageJ. An example of data analysis can be found in Figure 1F and S1E of Sin et al (2017). To quantify the relative amount of SDS-insoluble protein, a ratio (fold change) was calculated by dividing the values of Q40; moag-2/lir-3 mutants (undiluted sample of the point-mutation allele pk2183 and deletion allele tm813 shown on Figure 3B, top) by their corresponding wild-types ( wt , previously normalized to α-tubulin as a loading control).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ellen Nollen's (University of Groningen, The Netherlands) talk focused on genes that act as modifiers of aggregation, whose inactivation reduces aggregation and toxicity of polyQ (Glutamine) proteins without regulating their expression levels. Examples of such aggregation-modifying proteins include MOAG-2/LIR-3, a nuclear protein that is hijacked to the cytosol to promote aggregate formation (Sin et al, 2017), and MOAG-4/SERF2, which catalyses aggregation through direct and transient interaction with disease proteins, thus affecting the structure of the aggregate (Yoshimura et al, 2017).…”
Section: Modulation Of Protein Aggregation -Age and Other Factorsmentioning
confidence: 99%
“…lir-1 and lin-26 reside in an operon and together regulate differentiation 424 of non-neuronal ectodermal cells and the somatic gonadal epithelium(Boer et al 1998; 425 Dufourcq et al 1999;Bosher et al 1999). In contrast, lir-3 is a modifier of polyglutamine 426 aggregation in particular neurons and muscle cells(Sin et al 2017). Thus, LIR proteins 427 share similar zinc-fingers at their C-termini, but the roles of those domains are unknown, 428 and the proteins themselves appear to be functionally distinct.429 430 It is well established in other metazoans that co-regulators carrying LxxLL motifs, or "NR 431 boxes", activate or repress transcription (Heery et al 1997; Nolte et al 1998; Savkur and 432 Burris 2004; Loinder and Söderström 2004; Plevin et al 2005) by associating with the AF-433 2 domain near NR C-termini.…”
mentioning
confidence: 99%